Analysis of Factors Affecting Return on Assets - Istiana, Nikma; Rolanda, Ivo (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to analyze the factors influencing a company's financial performance, as measured by Return on Assets. The factors tested in this study include Working Capital Turnover, Sales Growth, Times Interest Earned Ratio, and Company Size. Methodology: This study examines the impact of of Working Capital Turnover, Sales Growth, Times Interest Earned and Company Size on Return On Assets, using data from 10 IDX listed pharmaceutical companies during 2018-2024. Companies were selected through purposive sampling. Data were sourced from the IDX website and analyzed using statistical methods, including multiple regression analysis using SPSS Version 25. Results: The results of this study indicate that there's a strong relationship between Times Interest Earned and Return On Assets. While Working Capital Turnover, Sales Growth, and Company Size do not affect Return On Assets. Conclusions: This study shows that the there's a strong relationship between Times Interest Earned and Return On Assets in pharmaceutical companies. This means that a company's ability to cover interest expenses with its operating profit is a key indicator in increasing asset profitability. Limitations: This study is limited by the number of pharmaceutical companies listed on the IDX during the 2018–2024 period. Contribution: This study strengthens financial theory the relationship between Times Interest Earned on Return on Assets, and offers practical insights for company in planning effective financing strategies.